Digital media, friendships and migrants’ entangled and non-linear inclusion and exclusion - Bork-Hüffer, Tabea (Urban studies, 2022)
In this article, I shed light on the role of digital media and friendships in migrants’ inclusion and exclusion. Connecting the empirical findings of a qualitative, non-media centric, multi-method study to existing research in digital migration studies, digital media and friendship as well as the literature on inclusion and exclusion, I propose the concept of entangled inclusion and exclusion. This perspective underlines migrants’ continuous (re-) negotiations of their situatedness in the (trans-)local spaces of the places they come from, move to and through. While playing diverse roles in migrants’ development and maintenance of (trans-) local friendships, digital media contribute to non-linearities in migrants’ subjective feelings of being included or excluded, making the processes involved more complex while also serving as material and symbolic signifiers of entangled inclusion and exclusion.
Gesehen am 10.04.2025
First published: September 2, 2022